Elderly Informal Workers and Elderly Supporting Capacity Ratio in Indonesia - Jamalludin Jamalludin (Program Studi Pendidikan Ekonomi, Universitas Insan Budi Utomo, 2020)
The proportion of the elderly population in Indonesia continues to increase. The implication of population aging is the low carrying capacity ratio which triggers the elderly to keep working. The need for leisure is increasing in the elderly, but almost half of the elderly in Indonesia still work. This study aims to look at the characteristics of the elderly who still work in the informal sector. This study also portrays the correlation between the carrying capacity ratio and social security ownership with the number of elderly workers by province. The secondary data used in this study is the 2018 national labor force survey data. The method used to answer this study is Pearson correlation analysis and binary logistic regression. The correlation analysis findings show that the higher the carrying capacity ratio of the elderly, the less elderly who work in a province. Social security in the elderly has a negative relationship with the number of elderly people who work. An interesting finding from the logit model is that the elderly with disabilities, both minor and moderate, are more inclined to work in the informal sector than the elderly who are not disabled. Low and secondary education in the elderly has a higher tendency to work in the informal sector than the elderly who have high education